Eucalyptus gasification using a multi-stage air gasifier: An experimental study - Andini A.; Aminuddin; Helios M.P.; Sajjakulnukit B.; Nasir S. (BIO Web of Conferences)
Eucalyptus is a fast-growing plant with high energy, so it is potential as a renewable energy source. Eucalyptus can be converted into synthesic gas containing CO and H2 for direct fuel or raw chemical production materials with gasification techniques. This paper reveals an experiment in which wood chips and pellets from Eucalyptus were processed in a multi-air-stage fixed bed downdraft gasifier to produce high-quality syngas. The temperature profile along the gasifier’s wall is measured, and the gas composition and the tar produced are analyzed. The result indicates that the eucalyptus biomass gasification in the proposed multi-stage-air gasifier adhered to the proper sequence of the downdraft gasifier and processed the biomass effectively, characterized by a low level of tar in the product gas.